2015
DOI: 10.1371/journal.pone.0132156
|View full text |Cite
|
Sign up to set email alerts
|

Population Difference in the Associations of KLOTH Promoter Methylation with Mild Cognitive Impairment in Xinjiang Uygur and Han Populations

Abstract: BackgroundMild cognitive impairment (MCI) is the intermediate stage of the cognitive changes between normal aging and dementia. KLOTH is an age-related gene that may contribute to the risk of MCI. The aim of our study was to explore the association between KLOTHO promoter methylation and MCI in Xinjiang Uygur and Han populations.MethodsDNA methylation assay was performed using the bisulphite pyrosequencing technology among 96 Uygur (48 MCI and 48 controls) and 96 Han (48 MCI and 48 controls) Chinese individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…45 Epigenetic modification, especially the DNA methylation, is emerging as a critical contributor to both acute and CKD progression. 18,48 Klotho promoter is characterized by typical CpG islands, and its differential methylation is associated with aging-related disorders 20 and various cancer conditions. 21,47 Elevated Klotho promoter methylation has been linked to the severity of CKD in patients and in uremic toxin-induced CKD in experimental animals.…”
Section: Rhein Derepression Of Klotho Protects Against Renal Damage Imentioning
confidence: 99%
See 1 more Smart Citation
“…45 Epigenetic modification, especially the DNA methylation, is emerging as a critical contributor to both acute and CKD progression. 18,48 Klotho promoter is characterized by typical CpG islands, and its differential methylation is associated with aging-related disorders 20 and various cancer conditions. 21,47 Elevated Klotho promoter methylation has been linked to the severity of CKD in patients and in uremic toxin-induced CKD in experimental animals.…”
Section: Rhein Derepression Of Klotho Protects Against Renal Damage Imentioning
confidence: 99%
“…18 Population-based genomewide quantitative evaluations of DNA methylation demonstrate that DNA hypermethylation and DNA hypomethylation occur at different loci in CKD. 18 Aberrant Klotho promoter methylation has been reported in aging-related disorders 19,20 and various cancers. 21,22 Recent studies further suggest that Klotho promoter hypermethylation is associated with the pathogenesis of acute kidney disease and CKD.…”
mentioning
confidence: 99%
“…CTAGE11P is a pseudogene and its function is unknown. Ethnic differences of DNA methylation in some genes have been reported, and DNA methylation of the two CpG sites in CTAGE11P might be affected in a similar manner.…”
Section: Discussionmentioning
confidence: 98%
“…CTAGE11P is a pseudogene and its function is unknown. Ethnic differences of DNA methylation in some genes have been reported, [30][31][32] and DNA methylation of the Table 1). CT, control.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have found that the promoter methylation of Klotho ( KL ) is ethnically different among Chinese Uygur and Han populations in Xinjiang. [25,26]…”
Section: Introductionmentioning
confidence: 99%